DEVELOPMENT OF A LEAK DETECTION SYSTEM OF LIQUEFIED PETROLEUM GAS (LPG) VIA LINE APPLICATION WITH AUTOMATED EMERGENCY RESPONSE SYSTEM - Yaipairoj, Saravut; Chunkag, Viboon; Sirisuk, Sasinapa; Jienmongkol, Seksan (Journal of Interdisciplinary Development (Humanities and Social Sciences), 2026)
The objectives of this research were: 1) to develop a Liquefied Petroleum Gas (LPG) leak detection system and 2) to design an automated emergency response and notification system via the LINE application to enhance safety and mitigate loss of life and property in households. The research instruments included the NodeMCU ESP8266 microcontroller integrated with a gas sensor (MQ-2), an infrared flame sensor (IR Flame Sensor), and a temperature sensor (DHT11). The system was designed to trigger emergency response outputs, including flashing signal lights, ventilation fans, and sprinkler pumps. The methodology employed an experimental and simulation-based design, with 20 trials conducted for each specified condition to evaluate system reliability. The results of the study revealed that: 1. Detection Efficiency: The system achieved 100% accuracy in detecting and notifying emergency situations across all tested conditions: 1) for gas leaks (>2% LEL), the system successfully sent LINE notifications and activated flashing lights; 2) for flame detection (>50°C), the system sent notifications and activated the sprinkler pump; and 3) for high-temperature detection (>50°C), the system sent notifications and activated the ventilation fan. 2. Response Performance: The device demonstrated an average processing and activation time of approximately 30 seconds per event, strictly adhering to the programmed logic within the microcontroller. The research concludes that the developed system is highly effective in automatically detecting and suppressing initial fire hazards. It serves as a viable prototype for smart safety devices in residential areas and small enterprises